Systematic review and meta-analysis of survival outcomes in T2a and T2b gallbladder cancers. Issue 6 (June 2022) - Alrawashdeh, Wasfi; Kamarajah, Sivesh K.; Gujjuri, Rohan R.; Cambridge, William A.; Shrikhande, Shailesh V.; Wei, Alice C.; Abu Hilal, Mohamed; White, Steve A.; Pandanaboyana, Sanjay
Abstract: Background: The 8th edition of AJCC TNM staging of Gallbladder cancer subdivided T2 stage into T2a and T2b based on tumour location. This meta-analysis aimed to investigate the long-term outcomes in T2a and T2b gallbladder cancers. Methods: Literature search of Medline, Web of science, Embase and Cochrane databases was performed. Study characteristics, survival and recurrence data were extracted for meta-analysis of effect estimates and of individual patient data. Results: Fifteen retrospective studies (2531 patients, T2a = 1332, T2b = 199) were included in the meta-analysis. Overall survival (OS) was significantly worse in patients with T2b compared to T2a tumours (HR 2.18, 95% CI 1.67–2.86, p < 0.0001). Meta-analysis of individual patient data (n = 629) showed similar results (HR 1.92, 95% CI 1.43–2.58, p < 0.00001). Patients with T2b tumours had higher risk of recurrence compared to T2a (OR 3.19, 95% CI 1.40–7.28, p = 0.006) and were more likely to receive adjuvant chemotherapy (OR 1.76, 95% CI 1.12–2.84, p = 0.014). Liver resection improved OS in T2b tumours (HR 2.99, CI 1.73–5.16, p < 0.0001). Conclusion: T2b gallbladder tumours have worse overall survival and increase risk of recurrence compared to T2a. Liver resection appears to improve OS in patients with T2b tumours. However, high quality multicenter data is required to confirm these results.